A method for recycling retired electrode materials
By mixing LiFePO4 and NCM811 in the waste lithium-ion battery with organic acid and processing, a sodium ion battery positive electrode material with an α-NaFeO2 layered structure was prepared, which solved the problem of low recycling efficiency of waste lithium-ion battery, and achieved efficient lithium separation and preparation of sodium ion battery materials, extending the battery's cycle life and reducing environmental pollution.
Patent Information
- Application Number
- CN202411741539.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-29
AI Technical Summary
In the prior art, the recycling efficiency of waste lithium-ion batteries is low, resulting in harmful chemicals and plastics that harm the ecological environment, and it is difficult to effectively utilize key materials in waste batteries.
By mixing waste LiFePO4 and NCM811 mixed with organic acid, heating and filtering, obtaining leachate liquid and filter residue, evaporation crystallization and acid leaching treatment, finally adding sodium source, manganese source and citric acid, calcining treatment, and preparing sodium ion battery positive electrode material with an α-NaFeO2 layered structure was prepared.
The efficient separation and recovery of lithium in waste lithium-ion batteries was achieved, and the positive electrode material of sodium ion battery with high initial specific capacity, good ion diffusion rate and structural stability was prepared, which extended the cycle life of the battery and reduced environmental pollution.
Smart Images

Figure CN119208800B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for recycling retired electrode materials, belonging to the field of recycling waste battery materials. Background Art
[0002] The development and popularization of lithium-ion batteries can effectively alleviate the shortage of non-renewable energy in power demand, especially in the electric vehicle and portable device industries. As the battery life expires, a large number of waste lithium-ion batteries are generated. It is estimated that by 2030, more than 1,100 tons of waste will be discarded. However, less than 5% of waste lithium-ion batteries have been recycled so far. At the same time, the harmful chemicals and plastics in waste batteries will harm the ecological environment, so the recycling of waste batteries is in urgent need of development. The composition of power batteries mainly consists of four key materials: positive electrode, negative electrode, diaphragm, and electrolyte. In the cost composition of lithium iron phosphate batteries, the proportion of positive electrode, negative electrode, diaphragm, and electrolyte are 40%, 10%, 8%, and 20% respectively. In 811 ternary batteries, the proportions are 57%, 7%, 4%, and 13% respectively. Whether in lithium iron phosphate batteries or ternary batteries, the cost of positive electrode materials accounts for the highest proportion, which is the core material of power batteries.
[0003] The main recycling technologies in the current market are direct recovery, pyrometallurgy and hydrometallurgy. Among them, newer methods such as direct recovery are highly dependent on the effective classification of battery types, and then determine the state of charge and capacity of the battery; high-temperature metallurgy converts metal oxides in battery materials into metals or metal compounds by heating. In reduction roasting, the battery material (after pretreatment) is heated under vacuum or inert atmosphere to convert metal oxides into mixed metal alloys containing cobalt, nickel, copper, iron and slag containing lithium and aluminum; hydrometallurgy mainly uses solutions to extract and separate metals from lithium batteries. Usually sulfuric acid and hydrogen peroxide are used for extraction, and hydrochloric acid, nitric acid and organic acids including citric acid and oxalic acid are also used. Once the metals are extracted into the solution, they are selectively precipitated as salts by pH agents, or directly used as the preparation solution of the positive electrode material precursor to directly obtain the regenerated positive electrode material.
[0004] Sodium-ion batteries have become the first choice for the next generation of batteries due to their lower cost, more stable electrochemical performance, and wider operating temperature range. Abundant sodium reserves are widely available around the world, showing the potential value of large-scale applications. Since lithium and sodium belong to the same main group, there is almost no difference in the physical and chemical properties between the elements. Therefore, sodium-ion batteries and lithium-ion batteries are very similar in structural design and working principles, and are suitable for devices in most applications.
[0005] Therefore, making full use of the leaching solution of waste lithium battery positive electrode materials LiFePO4 and NCM811, separating lithium and preparing sodium ion positive electrode materials, and comprehensively improving the electrochemical properties of sodium ion positive electrode materials, especially the initial specific capacity and the diffusion rate of sodium ions, is particularly important for further promoting the industrialization process of sodium ion batteries. Summary of the invention
[0006] The purpose of this application is to provide a simple and effective method for separating lithium from waste LiFePO4 and NCM811 mixed materials and preparing sodium ion positive electrode material regeneration, so as to solve the problems existing in the existing technology and promote the development of sodium ion batteries.
[0007] According to one aspect of the present application, a method for recycling retired electrode materials is provided, comprising the following steps:
[0008] 1) Mixing the waste electrode materials containing LiFePO4 and NCM811 with organic acid, heating, filtering, and obtaining a leaching solution and a filter residue;
[0009] 2) evaporating and crystallizing the leaching solution to obtain a product containing lithium phosphate;
[0010] 3) acid leaching the filter residue, adding a sodium source, a manganese source and citric acid, stirring, reacting, drying, calcining I, calcining II, and obtaining a positive electrode material for a sodium ion battery;
[0011] The chemical formula of the sodium ion battery positive electrode material is Na 1.05-1.1 Ni x Mn y Fe z Co 0.125x O2;
[0012] Where 1.125x+y+z=1, x=z, 0.1<y<0.35;
[0013] The sodium ion battery positive electrode material has an α-NaFeO2 type layered structure and belongs to the hexagonal R-3m space group.
[0014] The sodium ion battery positive electrode material has a smooth flat plate morphology. During the cycle, the flat plate morphology can better maintain its structural stability compared to the spherical and rod-shaped morphologies, and fewer intergranular cracks are formed during high-voltage charging, thereby effectively extending the cycle life of the battery. The fully exposed area and edge activity improve the reaction efficiency and reversibility of the electrochemical reaction.
[0015] The organic acid is selected from at least one of oxalic acid, acetic acid and formic acid.
[0016] The concentration of the organic acid is 0.2-1.5 mol / L.
[0017] Optionally, the concentration of the organic acid is any value among 0.2 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L, or a range between any two values.
[0018] The heating temperature is 60-90°C.
[0019] Optionally, the heating temperature is any value of 60°C, 70°C, 80°C, 90°C, or any range between two of them.
[0020] The temperature of the evaporation crystallization is 65-95°C.
[0021] Optionally, the temperature of the evaporation crystallization is any value of 65°C, 75°C, 85°C, 95°C, or any range between any two of them.
[0022] The acid used for the acid leaching is selected from at least one of nitric acid, acetic acid and oxalic acid, and the concentration is 0.5-2 mol / L.
[0023] The sodium source is selected from at least one of sodium carbonate, sodium nitrate and sodium acetate.
[0024] The manganese source is selected from at least one of manganese acetate tetrahydrate, manganese nitrate and manganese dioxide.
[0025] After adding sodium source and manganese source, the stoichiometric ratio of metal elements in the overall system is Na:Ni:Fe:Mn:Co=1.05~1.1:x:z:y:0.125x.
[0026] The amount of citric acid added is 1.3 to 1.5 times the molar amount of metal ions in the overall system after the sodium source and the manganese source are added.
[0027] The stirring time is 2 to 5 hours.
[0028] The reaction temperature is 70-90°C.
[0029] The drying temperature is 100-150°C.
[0030] The temperature of the calcination I is 400-550°C.
[0031] The heating rate of the calcination I is 3-10°C / min;
[0032] The calcination time is 3 to 7 hours.
[0033] The temperature of the calcination II is 700-1000°C.
[0034] The heating rate of the calcination II is 3-10°C / min.
[0035] The calcination time II is 10 to 15 hours.
[0036] The beneficial effects of this application include:
[0037] 1) First, use organic weak acid as a leaching agent to acid-leach the waste LiFePO4 and NCM811 mixed positive electrode materials. Different from traditional inorganic acids, the use of green and environmentally friendly organic weak acids can avoid the emission of harmful gases, such as chlorine, nitrogen oxides, and sulfur oxides, while also avoiding the increased difficulty of subsequent treatment of the leaching solution, equipment corrosion, and post-treatment of acidic wastewater. Environmental problems caused by inorganic acids. This method for this type of waste battery mixed material is scalable and can avoid screening of power batteries and reduce process flows.
[0038] 2) Direct lithium extraction technology is used to directly extract lithium from the leaching solution to avoid lithium loss and obtain lithium phosphate products; at the same time, high-purity valuable metal precipitates are obtained. For the separation of lithium, lithium is precipitated at a temperature close to the boiling point of water to obtain a precipitation rate of 75%~98%.
[0039] 3) Valuable metal filter residues are used to prepare positive electrode materials for sodium ion batteries through the sol-gel method and high-temperature calcination technology, expanding the preparation field of recycled positive electrode materials. Compared with commercial 111 sodium battery positive electrode materials, the sodium ion positive electrode materials obtained in this application will further increase the initial specific capacity due to the introduction of Co elements, show a higher ion diffusion rate, and have higher structural stability.
[0040] 4) The present invention adopts a waste recycling method to efficiently recover lithium from waste positive electrode materials and prepare sodium positive electrode materials. The introduction of Co improves the stability of the structure and the discharge specific capacity, achieving two goals with one stone, namely, recycling waste and modifying positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The Na prepared in Example 1 1.05 Ni 0.33 Mn 0.30 Fe 0.33 Co 0.04 XRD pattern of O2 sodium cathode material.
[0042] Figure 2 is the Na of Example 1 1.05 Ni 0.33 Mn 0.30 Fe 0.33 Co 0.04 SEM image of O2 sodium cathode material, scale is 1μm.
[0043] Figure 3 is the Na of Example 3 1.05 Ni0.40 Mn 0.15 Fe 0.40 Co 0.05 SEM image of O2 sodium cathode material, scale is 1μm. DETAILED DESCRIPTION
[0044] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0045] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0046] Embodiment 1:
[0047] 1) Place the waste LiFePO4 and NCM811 mixed positive electrode materials into 0.2 mol / L oxalic acid and heat at 70 °C for 2 h.
[0048] 2) Filter the step 1), and obtain the leaching solution 1, evaporate and crystallize at 65° C. to obtain a lithium phosphate product.
[0049] 3) Filter step 1) to obtain filter residue 1, dissolve it in 0.5 mol / L nitric acid, add sodium carbonate and tetrahydrate manganese acetate as sodium source and manganese source in the leaching liquid, and adjust the chemical dosage ratio to Na: Ni: Fe: Mn: Co = 1 + x: 0.33: 0.33: 0.3: 0.04, where x is 5%. Add citric acid, metal ion: citric acid = 1: 1.5 (molar ratio), stir for 2 hours, and then heat at 85°C to obtain wet gel, and then put it into a vacuum oven to dry at 125°C.
[0050] 4) The sample obtained in step 3) was calcined twice. The first sintering temperature was 500℃ and the temperature was kept for 6h; the second sintering temperature was 950℃ and the temperature was kept for 12h; the heating rate for both times was 5℃ / min, and Na 1.05 Ni 0.33 Mn 0.30 Fe 0.33 Co 0.04 O2.
[0051] Figure 1 The Na prepared in Example 1 1.05 Ni 0.33 Mn 0.30 Fe 0.33 Co 0.04 XRD diagram of O2 sodium positive electrode material. It can be seen from the figure that the regenerated positive electrode material conforms to the O3 crystal structure, indicating the successful preparation of pure phase sodium positive electrode material.
[0052] Figure 2This is a SEM image of the sodium positive electrode material of Example 1, with a scale of 1 μm. It can be seen from the figure that the regenerated positive electrode material exhibits a flaky morphology, and the surface is smooth, without the appearance of impurity phase, which is consistent with the XRD result.
[0053] (i=Li, Co, Ni, Fe, Mn)
[0054]
[0055]
[0056] Perform ICP test on the leaching solution to obtain the leaching rate L i and recovery rate R i In the formula, c i is the concentration of element i in the filtrate, v i The volume of the filtrate, m i is the mass of element "i" in the solid sample, and its m' Li is the mass of “Li” element in the Li precipitate.
[0057] Table 1: Leaching rate of lithium carbonate and valuable metals nickel, iron, cobalt and manganese in Example 1
[0058]
[0059] Table 2: Recovery of lithium carbonate and valuable metals nickel, iron, cobalt and manganese in Example 1
[0060]
[0061] As can be seen from the table, the method of the present application can achieve excellent metal element recovery rate.
[0062] Application in sodium ion batteries:
[0063] The prepared material was used as the positive electrode active material of sodium ion battery. A slurry consisting of 80% active material by mass, 10% Super P and 10% poly(vinylidene fluoride) (PVDF) in N-methylpyrrolidone (NMP) was coated on aluminum foil, then dried in a vacuum oven at 80°C, and cut into 12mm discs for use as positive electrodes. Metallic sodium with a diameter of 14mm was used as the negative electrode, and glass fiber with a diameter of 19mm was used as the separator. After 100 cycles at a current density of 0.5C, the capacity retention rate reached 90.42%.
[0064] Embodiment 2:
[0065] The process and conditions are the same as in Example 1, except that:
[0066] 1) Place the waste LiFePO4 and NCM811 mixed positive electrode materials into a 0.8 mol / L oxalic acid mixed solution and heat at 80 °C for 3 h.
[0067] 2) Filter the step 1), and obtain the leaching solution 1, evaporate and crystallize at 85° C. to obtain a lithium phosphate product.
[0068] 3) Filter the residue obtained in step 1) and dissolve it with 1 mol / L oxalic acid. Add sodium carbonate and tetrahydrated manganese acetate as sodium and manganese sources to the leaching liquid and adjust the chemical dosage ratio to Na: Ni: Fe: Mn: Co = 1 + x: 0.33: 0.33: 0.3: 0.04, where x is 7%. Add citric acid, metal ion: citric acid = 1: 1.5 (molar ratio), stir for 2 hours, and then heat at 85°C to obtain wet gel, which is then placed in a vacuum oven and dried at 125°C.
[0069] 4) The sample obtained in step 3) was calcined twice. The first sintering temperature was 500℃ and the temperature was kept for 6h; the second sintering temperature was 950℃ and the temperature was kept for 15h; the heating rate for both times was 5℃ / min, and Na 1.07 Ni 0.33 Mn 0.30 Fe 0.33 Co 0.04 O2.
[0070] Application in sodium ion batteries:
[0071] The prepared material was used as the positive electrode active material of sodium ion battery. A slurry consisting of 80% active material by mass, 10% Super P and 10% poly(vinylidene fluoride) (PVDF) in N-methylpyrrolidone (NMP) was coated on aluminum foil, then dried in a vacuum oven at 80°C, and 12mm discs were cut for use as positive electrodes. Metallic sodium with a diameter of 14mm was used as the negative electrode, and glass fiber with a diameter of 19mm was used as the separator. After 100 cycles at a current density of 0.5C, the capacity retention rate reached 85.26%.
[0072] Embodiment 3:
[0073] The process and conditions are the same as in Example 1, except that:
[0074] 1) Place the waste LiFePO4 and NCM811 mixed positive electrode materials into a 1.5 mol / L oxalic acid mixed solution and heat at 90 °C for 3 h.
[0075] 2) Filter the step 1), and obtain the leaching solution 1, evaporate and crystallize at 95° C. to obtain a lithium phosphate product.
[0076] 3) Filter step 1) to obtain filter residue 1, dissolve it with 1.5 mol / L acetic acid, add sodium carbonate and tetrahydrate manganese acetate as sodium source and manganese source in the leaching liquid, and adjust the chemical dosage ratio to Na: Ni: Fe: Mn: Co = 1 + x: 0.40: 0.40: 0.15: 0.05, where x is 5%. Add citric acid, metal ion: citric acid = 1: 1.3 (molar ratio), stir for 2 hours, and then heat at 85°C to obtain wet gel, which is then placed in a vacuum oven and dried at 125°C.
[0077] 4) The sample obtained in step 3) was calcined twice. The first sintering temperature was 500℃ and the temperature was kept for 6h; the second sintering temperature was 850℃ and the temperature was kept for 12h; the heating rate for both times was 5℃ / min, and Na 1.05 Ni 0.40 Mn 0.15 Fe 0.40 Co 0.05 O2.
[0078] Application in sodium ion batteries:
[0079] The prepared material was used as the positive electrode active material of sodium ion battery. A slurry consisting of 80% active material by mass, 10% Super P and 10% poly(vinylidene fluoride) (PVDF) in N-methylpyrrolidone (NMP) was coated on aluminum foil, then dried in a vacuum oven at 80°C, and 12mm discs were cut for use as positive electrodes. Metallic sodium with a diameter of 14mm was used as the negative electrode, and glass fiber with a diameter of 19mm was used as the separator. After 100 cycles at a current density of 0.5C, the capacity retention rate reached 82.14%.
[0080] Table 3 shows the Na content of Examples 1, 2 and 3. 1.05 Ni 0.33 Mn 0.30 Fe 0.33 Co 0.04 ICP data of O2 sodium cathode materials.
[0081] Table 3
[0082]
[0083] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for recycling retired electrode materials, characterized in that: The following steps are involved: 1) mixing the waste electrode material containing LiFePO4 and NCM811 with an organic acid, heating, filtering, and obtaining a leaching solution and a filter residue; 2) evaporating and crystallizing the leaching solution to obtain a product containing lithium phosphate; 3) acid leaching the filter residue, adding a sodium source, a manganese source and citric acid, stirring, reacting, drying, calcining I, calcining II, and obtaining a positive electrode material for a sodium ion battery; The chemical formula of the sodium ion battery positive electrode material is Na 1.05-1.1 Ni x Mn y Fe z Co 0.125x O2; Where 1.125x+y+z=1, x=z, 0.1<y<0.35; The sodium ion battery positive electrode material has an α-NaFeO2 type layered structure and belongs to the hexagonal R-3m space group; The organic acid is selected from at least one of oxalic acid, acetic acid and formic acid; The concentration of the organic acid is 0.2-1.5 mol / L.
2. The method for recycling retired electrode materials according to claim 1, characterized in that: The heating temperature is 60-90°C.
3. The method for recycling retired electrode materials according to claim 1, characterized in that: The temperature of the evaporation crystallization is 65-95°C.
4. The method for recycling retired electrode materials according to claim 1, characterized in that: The acid used for the acid leaching is selected from at least one of nitric acid, acetic acid and oxalic acid, and the concentration is 0.5-2 mol / L.
5. The method for recycling retired electrode materials according to claim 1, characterized in that: The sodium source is selected from at least one of sodium carbonate, sodium nitrate and sodium acetate; The manganese source is selected from at least one of manganese acetate tetrahydrate, manganese nitrate and manganese dioxide.
6. The method for recycling retired electrode materials according to claim 1, characterized in that: After adding the sodium source and the manganese source, the stoichiometric ratio of the metal elements in the overall system is Na:Ni:Fe:Mn:Co=1.05~1.1:x:z:y:0.125x.
7. The method for recycling retired electrode materials according to claim 1, characterized in that: The added amount of the citric acid is 1.3 to 1.5 times the molar amount of the metal ions in the overall system after the sodium source and the manganese source are added.
8. The method for recycling retired electrode materials according to claim 1, characterized in that: The stirring time is 2 to 5 hours; The reaction temperature is 70-90°C; The drying temperature is 100-150°C.
9. The method for recycling retired electrode materials according to claim 1, characterized in that: The temperature of the calcination I is 400-550°C; The heating rate of the calcination I is 3 to 10°C / min; The calcination time is 3 to 7 hours.
10. The method for recycling retired electrode materials according to claim 1, characterized in that: The temperature of calcination II is 700-1000°C; The heating rate of the calcination II is 3 to 10°C / min; The calcination II takes 10 to 15 hours.
Citation Information
Patent Citations
Method for regenerating sodium battery positive electrode material by using waste lithium manganate
CN115472948A
Method for preparing sodium-ion battery positive electrode material by recycling waste battery positive electrode (nickel cobalt lithium manganate) and application of sodium-ion battery positive electrode material
CN115611321A
Method for recovering lithium salt from waste lithium ion battery and preparing lithium manganese iron phosphate positive electrode material
CN118561254A